UPAYA MENINGKATKAN MINAT BELAJAR SISWA KELAS 2 MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATA PELAJARAN PENDIDIKAN PANCASILA SDN 1 TATURA PALU - Mega; Sri Mulyani; Deistamalina Musa (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to improve the learning interest of second-grade students at SDN 1 Tatura in the 2024/2025 academic year in Pancasila education through the Contextual Teaching and Learning (CTL) approach. Based on observations, it was found that the low learning interest hindered students' understanding of the material. Through the implementation of CTL in two cycles, test results showed a significant improvement, with classical mastery increasing from 23% at the baseline to 90% in cycle II. Furthermore, observations of both teacher and student activities also showed significant improvement, with scores of 91% and 90%, respectively. This study concludes that relevant learning connected to daily life and the use of engaging media can enhance students' interest and learning outcomes in Pancasila education